Evidence problems and materials - Friedland, Steven I.; Sahl, Jack P. (Durham, North Carolina : Carolina Academic Press, LLC, 2024)
'The seventh edition of Evidence Problems and Materials updates the evidence rules, provides new problems (especially about proposed rule additions), and emphasizes learning evidence law by analyzing problems. The book includes a wide variety of problems, from foundational to advanced, that are designed to provide students with feedback on how well they understand and apply the rules. Lastly, the book is based on neuroscience learning principles, including performance-tracking, quizzing, and spaced repetition, for better recall and deeper understanding. This book is intended for use in a basic evidence course. It includes all of the material necessary for those students who wish to become trial lawyers-and for those students who want to avoid the courtroom at all costs but still want to be well versed in the subject. It also includes a mock trial at the end to bridge the gap between a traditional evidence course and trial advocacy'--
Introduction to evidence -- The functions of judge, jury, and attorneys at trial -- Relevance [FRE 401,402] -- Unfairly prejudicial evidence [FRE 403] -- Character and habit evidence [FRE 404-406] -- Other exclusions of relevant evidence [FRE 407-415] -- The examination and impeachment of witnesses [FRE 607-615] -- The competency of witnesses [FRE 601-606] -- Opinions and expert testimony [FRE 701-706] -- Hearsay [FRE 801-807] -- The confrontation clause -- Privileges [FRE 501] -- Authentication, identification, and the best evidence rule -- Proof issues : the allocation of proof, judicial notice, and presumptions [FRE 201, 301, 302] -- Review problems.
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216393/ OC/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: Evidence (Law) -- United States; United States